PENGARUH KEPEMIMPINAN MEMBERDAYAKAN TERHADAP KETERIKATAN KERJA PEGAWAI DI LEMBAGA PEMASYARAKATAN KELAS IIA PEMATANGSIANTAR - Elok Narulita Puspa; Kusmiyanti (Jurnal Komunikasi Hukum, 2024)
This research aims to analyze the influence of empowering leadership on work engagement at the Lapas Kelas IIA Pematangsiantar. Empowering Leadership is assessed as a leadership behavior that is able to increase the meaning of work, encourage employee participation in decision making, demonstrate confidence in high performance and provide autonomy to employees over bureaucratic constraints. The research method used was quantitative with a survey approach involving all Lapas Kelas IIA Pematangsiantar employees as respondents. Data was obtained through a questionnaire and analyzed using Smart-PLS. The results of the research show that Empowering Leadership has a positive and significant influence on work engagement at the Lapas Kelas IIA Pematangsiantar. Leaders who apply empowering leadership will make employees feel more valued in decision making and increase their skills and be more enthusiastic about working. The age, gender, education level, length of work also have an influence in this research. This research concludes that there is a positive influence of Empowering Leadership on Work Engagement at the Lapas Kelas IIA Pematangsiantar. The level of influence of empowering leadership on work engagement at the Lapas Kelas IIA Pematangsiantar is 0.533 while the remaining 0.528 is influenced by other variables.